Itraconazole in combination with neutrophil depletion reduces the expression of genes related to pulmonary fibrosis in an experimental model of paracoccidioidomycosis (2018)
ABSTRACT: Itraconazole (ITC) is the drug of choice for treating paracoccidioidomycosis (PCM); nonetheless, patients with the chronic form of this mycosis develop fibrosis, a residual pulmonary abnormality, even after treatment. Recently, we observed that the depletion of neutrophils with a specific monoclonal antibody (mAb-anti-Ly6G) during the chronic stages of PCM was associated with a decrease in the fungal burden, the inflammatory response and a reduction of fibrosis. Herein, we aimed to evaluate the effect of ITC in combination with the mAb-anti-Ly6G in an experimental model of pulmonary PCM. BALB/c male mice were challenged with Paracoccidioides brasiliensis yeasts and treated with the mAb-anti-Ly6G and/or ITC at 4th week post-infection (p.i.) and then sacrificed at 12th week p.i. to assess neutrophil subpopulations, fungal load, collagen, expression of fibrosis- and pro-inflammatory-related genes and histopathology. We observed that combination of ITC/mAb-anti-Ly6G favored the control of infection and diminished the inflammatory response. Of note, such therapeutic strategy reduced the expression of IL-1β, IL-6, IL-17, IL-10, TNF-α, TGF-β1, TGF-β3, GATA-3, RORc, Ahr, MMP-1α, MMP- 8 MMP-15, TIMP-1, and TIMP-2 genes in an additive manner compared to those mice treated with the mAb or ITC alone. Interestingly, ITC induced an increase of type-II neutrophils even in those mice treated with the mAb-anti-Ly6G. These results indicate that combination ITC/mAb-anti-Ly6G reduced the infection and pulmonary fibrosis through down-regulation of inflammatory and pro-fibrotic genes. Additionally, we confirmed the immunomodulatory properties of this antifungal in vivo. This work emphasizes the importance of exploring new potential combination treatments to treat fungal infections.